The Influence of Celebrity Ambassador, Company Image and Service Quality on Rental Interest in Bassura City Apartments on Travelio.com - Yohanes Ferry Cahaya; Firda Aisyah Aisyah Pratiwi (Perbanas Institute, 2021)
This study aims to determine the effect of Celebrity Ambassador, Company Image and Service Quality on Rental Interest in Bassura City Apartments on Travelio.com. The research design used is an explanative research design, the type of research is descriptive quantitative research using a questionnaire. The sample technique uses probability sampling (simple random sampling) with 100 respondents. The analysis used is the correlation test, multiple linear regression, the coefficient of determination, and hypothesis testing. The results showed that: (1) Celebrity Ambassador has a significant effect on Rental Interest and has the smallest effect; (2) Corporate Image has a significant effect on Apartment Rental Interest and has the greatest influence (3) Service Quality has a significant effect on Apartment Rental Interest and has a greater influence on the Celebrity Ambassador variable and less than the Corporate Image variable. The F test shows if the regression model is considered feasible to predict the independent variable on the dependent variable. The R test shows that the independent variable is able to explain the dependent variable of rental interest by 58.6%. Keywords: Celebrity Ambassador, Company Image, Service Quality, Rental Interest